IMPLEMENTASI PENGAWASAN BAPAS PEKANBARU DAN KEJAKSAAN NEGERI PEKANBARU TERHADAP NARAPIDANA BEBAS BERSYARAT YANG MELAKUKAN TINDAK PIDANA DALAM MASA PERCOBAAN - Andika Surya; Erdianto Effendi; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
BAPAS is a institution to carry out community guidance. The prosecutor has the duty and authority to supervise the implementation of conditional criminal decisions, oversight criminal decisions, and conditional release decisions. The Purpose of this Research First; know the implementation of BAPAS and Attorney General's supervision of prisoners who are on parole who have committed crimes on probation. Second; know the obstacles in the implementation of supervision of BAPAS and the Prosecutor's Office on parole prisoners who commit crimes on probation.This type of research can be classified in the type of sociological juridical research, because in this study the authors directly conduct research at the location or place of study in order to provide a complete and clear picture of the problem under study. This research was conducted at BAPAS Pekanbaru and Pekanbaru District Attorney's Office, while the population and sample were all parties related to the problem examined in this study. The data source used is primary data and secondary data.From the research results there are two things that can be concluded, First; The form of supervision from BAPAS towards conditional free prisoners who commit criminal offenses on probation is to provide guidance to the correctional client. Until now the supervision of the prosecutor's office on parole inmates has almost never been carried out. Second, the obstacles of Bapas are the insufficient number of BAPAS Officers in conducting supervision; other than that the budget owned by BAPAS is insufficient, besides the lack of involvement of the Victim in the oversight. The juridical obstacle is that there are no clear rules regarding the rules governing the supervision of prisoners who are paroleed by the prosecutors. The non-juridical obstacle is the lack of inter-agency coordination (bapas and prosecutors) regarding the supervision of these conditional free prisoners. Author's advice, first; Bapas should carry out its function as a social guide better. In addition, the prosecutor's office as an institution that has the authority to oversee prisoners is on parole, must carry out its functions, not only to child prisoners. Second; Bapas should not make lack of budget, and lack of personnel as an excuse.Keywords : Implementation - BAPAS- Prosecutors (Kejaksaan) - Conditional Free Prisoners